An Overview Of EGCG And Its Potential Effects On Breast Cancer Cells (Journal of Pharmaceutical Negative Results, 2023)
Emperor Shennong a well-known character in Chinese brewed the first green tea. Green tea has the highest concentration of antioxidants of any tea and, is made from the processed leaf of Camellia Sinensis. This review has two parts, the first part explains an overview of green tea and its major polyphenol Epigallocatechin (EGCG), and the second part explains its therapeutic roles of it in the treatment of breast cancer cells. Green tea is processed and further EGCG is extracted depending on the technique and region. Among other phytochemicals, epigallocatechin is the richest phytochemical present in green tea, and also possesses therapeutic potential in the treatment of various disorders, among which treatment for cancer has been extensively researched. EGCG has various potential molecular targets involved in the processes like apoptosis, metastasis, growth factor, transcription, and cells cycle EGCGhave been postulated for its anticancer effects on breast cell carcinogenesis by inducing cell death via apoptosis, inducing autophagy, interacting with cellular oxidative stress levels, inhib ting metastasis, and inhibiting tumor angiogenesis.